Reactive oxygen species in cancer progression and its role in therapeutics - Ranjeet Singh; Partha Pratim Manna (Open Exploration Publishing Inc., 2022)
The redox status in pathogenesis is critically regulated by careful balance between the generation of reactive oxygen species (ROS) and their elimination. Increased ROS level above the cellular tolerability threshold results in apoptotic or necrotic cell death. ROS belongs to a group of highly reactive compounds that have evolved to play key roles in cellular signaling pathways. It's widely assumed that a reasonable amount of ROS is essential for a variety of biological processes. Elevated levels of ROS are known to cause various pathologic conditions like neurological disorders, cardiovascular conditions, inflammation, autoimmunity, and cancer. ROS is well known to initiate and assist in progression of tumor by promoting proliferation and survival of cancer cells and thus facilitates pro-tumorigenic signaling in tumor microenvironment. As cancer cells become more resilient to the effects of ROS manipulating drugs, increased antioxidant capacity attenuates their susceptibility to cancer treatment. Excessive environmental stress, on the other hand, can cause cancer cells to die. This review summarizes various molecular mechanisms including the role of checkpoint inhibitors that can be harnessed to develop effective therapeutic strategies for targeting ROS related signaling in cancer.